Proteotyping to establish gene origin within reassortant influenza viruses. - Ji-won Ha (Public Library of Science (PLoS), 2011)
The application of a rapid and direct proteotyping approach with which to identify the gene origin of viral antigens in a reassortant influenza strain is demonstrated. The reassortant strain, constructed for a vaccine against type A 2009 H1N1 pandemic influenza, contains genes derived from a wild-type pandemic strain (A/California/7/2009) and an egg adapted high-growth strain (denoted NYMC X-157) derived from an earlier A/Puerto Rico/8/34 strain. The proteotyping approach employs modern proteomics methods and high resolution mass spectrometry to correctly establish that the genes of the surface antigens, hemagglutinin and neuraminidase, are derived from the A/California/7/2009 strain while those for nucleoprotein and matrix protein M1 antigens are derived from the NYMC X-157 strain. This is achieved for both gel-separated antigens and those from a whole vaccine digest. Furthermore, signature peptides detected in the mass spectra of the digested antigens enable the engineered reassortant strain to be identified as a type A virus of the H1N1 subtype in accord with earlier studies. The results demonstrate that proteotyping approach provides a more direct and rapid approach over RT-PCR with which to characterize reassortant strains of the influenza virus at the molecular protein level. Given that these strains pose the greatest risk to human and animal health and have been responsible for all human pandemics of the 20th and 21st centuries, there is a vital need for the origins and evolutionary history of these strains to be rapidly established.